ANALISIS SEKTOR PERTANIAN UNGGULAN DI KABUPATEN GUNUNGKIDUL - Rijal Nurhidayat; Lestari Rahayu Waluyowati; Ari Astuti (Fakultas Pertanian UST, 2022)
The objectives of this study were (1) to determine the role of the agricultural sector in Gunungkidul Regency, (2) to determine the factors that influence the growth of the agricultural sector and agricultural sub-sector in Gunungkidul Regency, and (3) to identify changes in patterns and structures in the agriculture, forestry, and fisheries sub-sectors. The research was conducted using descriptive quantitative methods. The data used in this study are secondary data, including business field GRDP data based on constant prices in Gunungkidul Regency and business field GRDP based on constant prices in the Special Region of Yogyakarta. The analytical methods used in this study are Location Quontient analysis, Dynamic Location Quontient analysis, Shift Share analysis, and Klassen Typology analysis. According to the results of this study could be concluded that the agricultural sector is a potential superior sector developed in the future and the agricultural sub-sector which is the superior sub-sector is the Food Crop Sector and Forestry Sub-Sector from the results of LQ analysis> 1, which indicates that the contribution of the agricultural sector can be on income. There are changes in the role of the agricultural sub-sector, these changes include the Food Taffe Sub-Sector subject to the base to non-base, and plantation sub-sectors, livestock, agricultural, fishing services, and fisheries change from non-base to base, know the comparison of the results of LQ analysis and the factors that influence the growth of the agricultural sector and the superior agricultural sub-sector, namely the state of the economy outside the region of the region of the competitive region that can be known through the results of the Shift Share analysis that shows the provincial share and differential shift. This grouping show that the agricultural sector as the food crop and forestry sub-sectors are still the main priority in development in Gunungkidul Regency.